Preventing Gray Hole Attack using AOTMDV Routing protocol in MANE (International Journal of Engineering and Computer Science, 2017)
MANETs are autonomous and decentralized networks. It is accessible to both genuine users and malicious attackers. In the network services, confidentiality and integrity of the data is affected due to security issues. MANETs are very vulnerable to various attacks from malicious nodes, some classical malicious attacks (eg., DoS attacks, warm-hole attack, gray-hole attack and black-hole attack). In this paper, we are calculating the trust value of nodes using decision factors such as direct degree and recommendation degree. We focus on further improvement of routing, trust based Ad-hoc On-demand Multi-path Distance Vector Routing (AOTMDV) protocol is used, which is an extension form of Ad-hoc On-demand Multi-path Distance Vector Routing (AOMDV) protocol. AOTMDV protocol is to incorporate other decision factors (Incentive function and Active degree) to improve the trust. By enhancing the trust, gray hole attacks will be prevented and the performance of network throughput, packet delivery ratio and malicious attack resistance also improved effectively.